Advancing diabetic wound care: The role of copper-containing hydrogels - Mohammad Ebrahim Astaneh; Narges Fereydouni (Heliyon)
Diabetic wounds pose a significant challenge in healthcare due to their complex nature and the difficulties they present in treatment and healing. Impaired healing processes in individuals with diabetes can lead to complications and prolonged recovery times. However, recent advancements in wound healing provide reasons for optimism. Researchers are actively developing innovative strategies and therapies specifically tailored to address the unique challenges of diabetic wounds. One focus area is biomimetic hydrogel scaffolds that mimic the natural extracellular matrix, promoting angiogenesis, collagen deposition, and the healing process while also reducing infection risk. Copper nanoparticles and copper compounds incorporated into hydrogels release copper ions with antimicrobial, anti-inflammatory, and angiogenic properties. Copper reduces infection risk, modulates inflammatory response, and promotes tissue regeneration through cell adhesion, proliferation, and differentiation. Utilizing copper nanoparticles has transformative potential for expediting diabetic wound healing and improving patient outcomes while enhancing overall well-being by preventing severe complications associated with untreated wounds. It is crucial to write a review highlighting the importance of investigating the use of copper nanoparticles and compounds in diabetic wound healing and tissue engineering. These groundbreaking strategies hold the potential to transform the treatment of diabetic wounds, accelerating the healing process and enhancing patient outcomes.